Application of aeromagnetic data to gold exploration in northeastern Ontario - Raymond J. Pichette (Canadian Institute of Mining, Metallurgy and Petroleum, 1982)
"Aeromagnetic data can be useful in helping to delineate structures and rock types in gold exploration. Magnetic anomalies associated with Archean volcanic belts in northeastern Ontario can be quickly and effectively analyzed in profile form with the use of model curves. The model curves help to locate contacts between strata. They also help to estimate the magnetite content of the rocks and their depth beneath overburden.An aeromagnetic map of part of Catharine Township, Ontario has been analyzed with the aid of model curves. Several magnetic rock types, potential fault zones and areas of relatively thick overburden were delineated.IntroductionIn any exploration program, a good understanding of the stratigraphy, rock types and structure enhances the possibility of success. For example, environments which host gold deposits in the Abitibi Volcanic Belt may be characterized as follows (Jensen, 1980; Pyke, 1980):(I) They have major faults, especially as tectonic boundaries between volcanic piles which include mafic and ultramafic rocks and clastic sedimentary rocks or gneisses.(2) They have subvolcanic felsic intrusions.(3) They have extensive carbonitization, with or without carbonate and sulphide-facies iron formation.In all cases, delineation of structure and rock type should be a major objective in exploration. The analysis of magnetic data can be a useful tool in this task. This paper is presented with the purpose of describing the application of the magnetic method to gold exploration in Archean volcanic terrains.Magnetic AnalysisTotal-intensity magnetic contour maps can be used to discriminate rock units according to differences in magnetization. However, because of smoothing of texture resulting from the compilation procedure and the fact that survey lines are widely spaced, contours should not be directly used for quantitative analysis. A much more definitive means of magnetic analysis is provided by the use of the original profile or chart recordings. Model curves provide a basis for analyzing these profiles both accurately and rapidly."